1987
DOI: 10.1016/0889-1591(87)90031-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the immune response by POMC-derived peptides

Abstract: The POMC-derived peptides (5endorphin and ACTH are capable of modulating an immune response in physiological concentrations. These neuropeptides can either enhance or inhibit the proliferative response of human peripheral blood lymphocytes after stimulation with the mitogen concanavalin A. The modulatory action of the peptides is not only dependent on the concentration but appears to be donor dependent. The response pattern observed is not determined by a selective affinity for certain amino acid sites on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…2). A comparable bimodal dose-response curve could also be observed for the modulatory effect of P-endorphin on the proliferative response of Tcells after stimulation with the Tcell mitogen Con A [14].…”
Section: Cell Lysis and Immunoprecipitationsupporting
confidence: 52%
See 1 more Smart Citation
“…2). A comparable bimodal dose-response curve could also be observed for the modulatory effect of P-endorphin on the proliferative response of Tcells after stimulation with the Tcell mitogen Con A [14].…”
Section: Cell Lysis and Immunoprecipitationsupporting
confidence: 52%
“…There is pharmacological evidence, obtained from functional assays, for the presence of opiate binding sites on lymphocytes (reviewed in [15]). However, it has been demonstrated that p-endorphin can also influence immune responses such as antibody synthesis and T cell proliferation via a non-opiate receptor-mediated mechanism [14][15][16][17]. Binding of P-endorphin to opiate receptors can be prevented by acetylation of the N terminus of the peptide [18].…”
Section: Cell Lysis and Immunoprecipitationmentioning
confidence: 99%
“…Increases in cortisol, for instance, are associated with immunomodulation, especially with decreases in circulating lymphocytes (62). Depending on the metabolic state of the lymphocytes, results (in vitro) show both inhibitory as well as facilitating effects of /3-endorphin on the proliferation of lymphocytes (63,64). Depending on the metabolic state of the lymphocytes, results (in vitro) show both inhibitory as well as facilitating effects of /3-endorphin on the proliferation of lymphocytes (63,64).…”
Section: Recoverymentioning
confidence: 99%
“…Concerning T-lymphocyte activation, both stimulatory (Fontana et al, 1987;Gilman et al, 1982;Gilmore and Weiner, 1989;Heijnen et al, 1987;Kusnecov et al, 1987;van den Bergh et al, 1991b) and inhibitory (Manfredi et al, 1993;McCain et al, 1982;Panerai et al, 1995;Puppo et al,1985) effects of h-endorphin on lymphocyte proliferation have been described. The action on Th1/Th2 cytokines is also controversial: both enhancement (Bessler et al, 1990;van den Bergh et al, 1991b) or inhibition (Garcia et al, 1992) of IL-2 production by h-endorphin were described.…”
Section: Introductionmentioning
confidence: 99%